The Influence of Occupational Stress and Mental Health on Nigerian Police Officers’ Aggression - Oscar, Yomi Akindele -; Bello, Subaedat Opeyemi; Aborishade, Richard (NIU Journal of Social Sciences, 2019)
The study investigated the influence of occupational stress and mental health on Nigeria Police Officers’ aggressivity. Agressivity by the police is widespread, consistent, persistent and multidimensional in Nigeria. The study is a descriptive survey research in which occupational stress and mental health were the independent variables and police aggressivity as the dependent variable. The participants responded to three valid and standardized instruments which were: The Aggression Questionnaire (TAQ), Operational Police Stress Questionnaire (PSQ-OP), and Mental Health Inventory (MHI-18). Multiple regression statistics was used to analyse the data collected. The results obtained indicated that occupational stress and mental health jointly and relatively contributed significantly to the Prediction of Nigerian Police aggressivity (F = 2.456, R 2 = .623 P < 0.05). On the basis of this finding, it is concluded that there is a need to develop intervention to reduce aggressivity among Nigerian police officers. It is recommended that the Police Serve Commission and Police Authority should be more proactive by identifying police officers with potentials for aggressivity through diagnoses by Counseling/Correctional Psychologists who could assist such police officers deal with their aggression problems. The current reactive measures (punitive) meted out by Police Authority to culpable police officers guilty of aggressivity that has not reduced the menace should be revised, and or reviewed, particularly in the current democratic dispensation. Keywords: Police Officers’ Aggressivity, Occupational Stress, Mental Health